Addressing School-Community Relations in a Cross-Cultural Context: A Collaborative Action to Bridge the Gap Between First Nations and the School - Seth A. Agbo (Journal of Research in Rural Education, 2007)
The search for new designs for improving parent involvement is a common issue in many schools today. The notion of local control of education in First Nations communities in Canada is directly linked to the need for parental involvement in schooling. This study utilizes a participatory research approach to examine views on community involvement expressed by Euro-Canadian teachers as well as those of First Nations parents. Results indicate that for collaborative school-community relations to thrive in First Nations communities, the school must empower the community through genuine discussions that foster collaboration and respect for multiple perspectives. The perception of collaboration should depend both on the values and exigencies in the community and on the values, dispositions, and capabilities of teachers. First Nations education must therefore be reformulated in accordance with a different, non-Eurocentric referent, and the education and training of teachers for First Nations students should be fi rmly divorced from any association with the idea of Eurocentric schools.